An analysis of digital stories of self-care practices among first- year students at a university of technology in South Africa (Journal of Student Affairs in Africa, 2023)
This article reports on a qualitative study that explored self-care practices among first-year studentsin managing stressors related to the first-year experience in the context of the COVID-19 pandemic.Qualitative data were collected using a purposive sample between March and June 2022. A total of 26first-year students registered at a university of technology in South Africa participated in the study byproducing digital stories sharing how they practised self-care. The domains of self-care were adoptedas a framework and data were analysed using thematic analysis. Six domains of self-care practicesemerged from the data and were categorised as physical, emotional, spiritual, relational, professional,and psychological. The findings show that first-year students engaged in a range of self-care practicesacross the domains of self-care including exercising, listening to music, performing ancestral rituals,donating blood, following successful people on social media, and learning new skills. Further,relational self-care was the most fundamental domain that underpinned first-year students’ well-being. In contrast, oversleeping or sleep deprivation, reckless spending, and eating unhealthy foodto cope with stressors related to the first-year experience pointed to unhealthy self-care practicesin managing the stressors. Unhealthy self-care practices can threaten first-year students’ well-beingand possibly academic success. Student affairs and services need to design self-care programmes andcurricula to prevent harm and support adequate self-care. In designing self-care programmes, socialinvolvement and engagement are fundamental principles that should be emphasised. Future studiescan develop a self-care inventory to identify students at risk of poor self-care and design targetedinterventions to promote self-care.